PARTISIPASI MASYARAKAT DALAM UPAYA PENCEGAHAN STUNTING DI KELURAHAN PEDURUNGAN KIDUL KECAMATAN PEDURUNGAN KOTA SEMARANG - Nafi’a, Akhi Sulisun; Malik, Abdul (Jurnal Review Pendidikan dan Pengajaran, 2024)
Community participation is needed in every government program, especially in cases of stunting which have not been optimally resolved until now. The high rate of stunting in Indonesia shows a lack of community participation in participating in stunting prevention programs. The purpose of this study was to analyze the participation of the Pedurungan Kidul Village community, efforts made to prevent stunting and the obstacles experienced. This study uses a qualitative descriptive approach by identifying the stages and forms of community participation, stunting prevention efforts and obstacles that occur when the program is implemented. Data collection was obtained through interviews, observations and documentation. Informants in the interview were posyandu cadres, Pedurungan Kidul Village health workers, stunting officers. Data analysis was carried out through three stages, namely data reduction, data presentation and drawing conclusions. The results of the study showed that the Pedurungan Kidul Village community actively participated in efforts to prevent stunting cases, this participation was in the form of participation of ideas, participation of labor, participation of goods and participation of money (funds). The efforts made were to provide additional food or snacks and socialize the problem of stunting. However, in these efforts there are still obstacles that arise such as the presence of working mothers, mothers who are less educated and lack of motivation of posyandu cadres. This study concludes that assistance and participation from the community and support from the sub-district government and health centers will result in optimal stunting prevention efforts.